Exposure of Nubian ibex (Capra nubiana) to humans reduces behavioural responses to potential threats - Yuval Zukerman; Oded Berger‐Tal (People and Nature, 2024)
Abstract The spatial expansion of human populations has increased the overlap between humans and wildlife, leading to the greater tolerance of many wildlife species to humans. However, our current understanding of the consequences of such tolerance is limited. In particular, we lack information on whether reduced behavioural responses to humans are indicative of reduced responses to other potential threats. We made use of a unique natural system comprising geographically adjacent, but nevertheless separate, populations of the threatened Nubian ibex (Capra nubiana) that are exposed to different levels of human disturbance to test the effects of exposure to humans on ibex behavioural responses to other stimuli. We measured flight initiation distance (FID) and alert distance (AD) in males approached by four different stimuli: a human, a human with a dog, a novel object, and a leopard model. Both FID and AD decreased for all stimuli as the human exposure level increased. Ibex in areas that are highly exposed to humans reduced their behavioural responses to humans more strongly compared to other stimuli. These findings suggest that tolerance for humans may be the product of several complementary behavioural mechanisms (such as habituation and non‐random dispersal). Policy implications. Our findings align with the concern that animals highly exposed to human beings may be less capable of surviving in the wild. Our results also emphasize that the interactions between people and wild animals (such as feeding them) determine the behavioural responses of wild animals, shaping patterns of human–wildlife conflict and co‐existence. Read the free Plain Language Summary for this article on the Journal blog.